DEVELOPMENT OF PROGRAM TO ENHANCE DIGITAL LEADERSHIP OF SCHOOL ADMINISTRATORS UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE KALASIN - Moonsap, Waiyawit; Srisaard, Boonchom (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The research aimed to 1) to study the current conditions, desirable conditions, and the needs of digital leadership of school administrators under the Secondary Educational Service Area Office Kalasin and 2) to develop the digital leadership enhancement program of school administrators under the Secondary Educational Service Area Office Kalasin. The research is mixed method. The sample group was school administrators and teachers amount 369 people under the Secondary Educational Service Area Office Kalasin. The informants were school administrators or deputy school administrators amount 1 person and head of department or the chief of administration subdivision amount 1 person from 3 schools that were good practices totally 6 people finding by purposive sampling. Moreover, there were 9 experts who assessed the suitability and feasibility of the program finding by purposive sampling. Research instruments were questionnaire, semi-structured interview and appropriateness and feasibility assessment of the program. The frequency, percentage, means, standard deviation, Pearson product-moment correlation, Cronbach’s alpha coefficient and Modified Priority Needs Index (PNImodified) were employed to analyze data. The findings of this research were as follows: 1) the overall current condition of digital leadership of school administrators was in the high level. Moreover, the desirable conditions of digital leadership of school administrators was in the highest level and the priority of needs on enhancing digital leadership of school administrators under the Secondary Educational Service Area Office Kalasin was sorted in descending order including digital literacy and use, digital vision and communication and ethics digital, respectively.2) The program to enhance digital leadership of school administrators under the secondary educational service area office Kalasin consisted of 1) principle 2) objectives 3) content which divided into 3 modules : module 1 digital vision, module 2 digital literacy and use, module 3 communication and ethics digital 4) the developing principals as 70-20-10 model. Developing methods consisted of workshop, real practice and study and research for self-improvement 5) program assessment. The assessment result found that both of suitability and feasibility of the program to enhance digital leadership of school administrators under the secondary educational service area office Kalasin were in the highest level.